MODAL SOSIAL DAN KEWIRALEMBAGAAN DALAM PROGRAM HUTAN SOSIAL OLEH PT PAITON ENERGI - Rahman, Nuril Endi; Ibrahim, Malik; Saputri, Ferra Wulan (Social Welfare Study Program, 2024)
Abstract. The social forest programme is one of the important pillars of development that contributes to reducing land tenure inequality and alleviating poverty, which refers to the principles of the green economy. This study aims to describe the management of social forest programmes that utilise social capital by KTH Ranu Makmur and Alam Subur, and describe the extent of the institutional factors applied by KTH Ranu Makmur and Alam Subur in managing social forests. The research method used qualitative case study method. Data collection techniques used participatory observation, in-depth interviews, FGDs and document studies. Data analysis was conducted inductively with the stages of data reduction, data organisation, memoing and coding, data categorisation and empirical generalisation. The results showed that in its implementation, KTH Ranu Makmur and Alam Subur, which had previously existed, utilised social capital as a group strength in managing forest land for agriculture. The institutional factor is also a reinforcement for the group, with the social orientation that makes the group more resilient. The utilisation of social capital by Ranu Makmur and Alam Subur groups makes it easier for the group to deal with various problems such as difficulties in agricultural raw materials, with the network owned by the group, the members of KTH can provide information related to access to agricultural raw materials such as fertilisers and coffee plant seeds. Social capital owned by KTH is also reflected in agricultural activities, such as during the planting period where group members help each other to reduce costs. The social forest programme, especially for Ranu Makmur and Alam Subur, has contributed to poverty alleviation and forest conservation. Keywords: Social forest; social capital; entrepreneurship. Abstrak. Program hutan sosial merupakan salah satu pilar penting pembangunan yang berkontribusi untuk mengurangi ketimpangan penguasaan lahan dan mengentaskan kemiskinan, yang mengacu pada prinsip ekonomi hijau. Tujuan penelitian ini untuk menggambarkan pengelolaan program hutan sosial yang memanfaatkan modal sosial oleh KTH Ranu Makmur dan Alam Subur, dan menggambarkan sejauhmana faktor kewiralembagaan yang diterapkan oleh KTH Ranu Makmur dan Alam Subur dalam mengelola hutan sosial. Metode penelitian menggunakan metode kualitatif jenis studi kasus. Teknik pengumpulan data penelitian menggunakan teknik observasi partisipatif, wawancara mendalam, FGD, dan studi dokumen. Analisis data penelitian dilakukan secara induktif dengan tahapan reduksi data, pengorganisasian data, pembacaan memoing dan koding, kategorisasi data dan generalisasi empiris. Hasil penelitian menunjukkan bahwa dalam pelaksanaannya KTH Ranu Makmur dan Alam Subur yang sebelumnya telah eksis, kemudian memanfaatkan modal sosial sebagai kekuatan kelompok dalam mengelola lahan hutan untuk pertanian. Faktor kewiralembagaan juga menjadi penguat bagi kelompok, dengan adanya orientasi sosial sehingga menjadikan kelompok lebih memiliki resiliensi. Pemanfaatan modal sosial oleh KTH Ranu Makmur dan Alam Subur memudahkan kelompok dalam menghadapi berbagai persosalan seperti kesulitan bahan baku pertanian, dengan adanya jaringan yang dimiliki oleh kelompok maka antar anggota KTH dapat saling memberikan informasi terkait akses bahan baku pertanian seperti pupuk dan benih tanaman kopi. Modal sosial yang dimiliki oleh KTH juga tergambar dalam aktivitas pertanian, seperti pada saat masa tanam di mana antar anggota kelompok saling membantu sehingga dapat menekan biaya. Program hutan sosial khususnya bagi KTH Ranu Makmur dan Alam Subur, telah berkontribusi dalam pengentasan kemiskinan dan menjaga kelestarian hutan. Kata Kunci: Hutan sosial; modal sosial; kewiralembagaan.